Cullin 4A (CUL4A), a direct target of miR-9 and miR-137, promotes gastric cancer proliferation and invasion by regulating the Hippo signaling pathway - Deng, Jun (Oncotarget, 2016)
Although Cullin 4A (CUL4A) is mutated or amplified in several human cancer types, its role in gastric cancer (GC) and the mechanisms underlying its regulation remain largely uncharacterized. In the present study, we report that the expression of CUL4A significantly correlated with the clinical stage of the tumor and lymph node metastasis, and survival rates were lower in GC patients with higher levels of CUL4A than in patients with lower CUL4A levels. The upregulation of CUL4A promoted GC cell proliferation and epithelial-mesenchymal transition (EMT) by downregulating LATS1-Hippo-YAP signaling. Knocking down CUL4A had the opposite effect in vitro and in vivo. Interestingly, CUL4A expression was inhibited by the microRNAs (miRNAs), miR-9 and miR-137, which directly targeted the 3′-UTR of CUL4A. Overexpression of miR-9 and miR-137 downregulated the CUL4A-LATS1-Hippo signaling pathway and suppressed GC cell proliferation and invasion in vitro. Taken together, our findings demonstrate that perturbations to miR-9/137-CUL4A-Hippo signaling contribute to gastric tumorigenesis, and suggest potential therapeutic targets for the future treatment of GC.